The Book of Daniel and the Apocryphal Daniel Literature - Ditommaso, Lorenzo (Leiden Brill, 2005)
This volume illuminates the full extent of the ancient and mediaeval apocryphal texts associated with or attributed to Daniel (including the Daniel legenda, the apocryphal apocalypses, and the prognostica) and investigates their relationship with the bibl
Keywords: Bible. -- Daniel -- Criticism, interpretation, etc. Bible. -- History of Susanna -- Criticism, interpretation, etc. Bible. -- Bel and the Dragon -- Criticism, interpretation, etc. Daniel-Diegese -- Criticism, interpretation, etc. Syriac Apocalypse of Dani